Novel and Innovative Surgical Strategies for Recurrent Rectal Cancer: Uncommon Resections, Local Interventions for Pelvic Reoccurrence, and Intraoperative Radiation Therapy - Webb, Shawn Philip; Ahmad, Imran (Clinics in Colon and Rectal Surgery, 2023)
The frequency of recurrent rectal cancer has dropped significantly with improved surgical approaches and adjunctive therapies. These recurrences have proven challenging to obtain R0 resection with salvage operations. Meticulous planning, clear understanding of anatomy with imaging, and multispecialty support have become essential in local control and long-term survival with pelvic recurrence of rectal cancer. Technical considerations and prognosis indicators along with role of intraoperative radiation or boost radiation are discussed within.
Keywords: recurrent rectal cancer; colon and rectal surgery